Do climate engineering experts display moral-hazard behaviour? - Christine Merk; Gert Pönitzsch; Katrin Rehdanz (Climate Policy, 2018)
Discourse analyses and expert interviews about climate engineering (CE) report high levels of reflectivity about the technologies' risks and challenges, implying that CE experts are unlikely to display moral hazard behaviour, i.e. a reduced focus on mitigation. This has, however, not been empirically tested. Within CE experts we distinguish between experts for radiation management (RM) and for carbon dioxide removal (CDR) and analyse whether RM and CDR experts display moral hazard behaviour. For RM experts, we furthermore look at whether they agree to laboratory and field research, and how they perceive the risks and benefits of one specific RM method, Stratospheric Aerosol Injection (SAI). Analyzing experts' preferences for climate-policy options, we do not find a reduction of the mitigation budget, i.e. moral hazard, for RM or CDR experts compared to climate-change experts who are neither experts for RM nor for CDR. In particular, the budget shares earmarked for RM are low. The perceptions of risks and benefits of SAI are similar for RM and climate-change experts. Despite the difference in knowledge and expertise, experts and laypersons share an understanding of the benefits, while their perceptions of the risks differ: experts perceive the risks to be larger.
Keywords: 330; Stratospheric Aerosol injection (SAI); climate engineering; geoengineering; risk perception; expert perception; moral hazard